Template-induced Bi2O2CO3 microstructure self-assembled by nanosheets with exposed {001} facets. (6th June 2018) - Cheng, Lijun; Hu, Xumin; Hao, Liang
Abstract: Bi2 O2 CO3 microstructures self-assembled by nanosheets with exposed {001} facets were synthesized via a facile cetyltrimethyl ammonium bromide (CTAB)-assisted hydrothermal process. X-ray diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET) surface area analysis, X-ray photoelectron spectroscopy (XPS), UV–vis diffuse reflectance spectroscopy (UV–vis DRS) and Photoluminescence (PL) spectra were used to characterize the as-prepared samples. Compared to Bi2 O2 CO3 microstructure obtained without any template, the template-assisted Bi2 O2 CO3 microstructure demonstrated enhanced photocatalytic activity, which mainly resulted from exposure of {001} facets, narrower band gap and less recombination of charge carriers. When the addition amount of CTAB was 0.6 g, the exposure percentage of {001} facets was largest, the band gap smallest and charge carrier separation most effective, giving rise to highest photoreactivity for RhB degradation. Approximately 97.67% of RhB degradation efficiency was achieved within 45 min. Moreover, holes were proved to be the dominant active species in the photocatalytic process.